Use of aldrete and kroulik index in the post anesthetic recovery room: a systematic review - Claudinalle Farias Queiroz de Souza; Luana Ketlen Cavalcanti de Lima Felix; Keity Ranielly do Amaral Silva; Lara Roberta de Moura; Maria Eduarda Pereira de Almeida; Letícia Patrícia de Oliveira Nóbrega; Liana Gabriele da Cruz Mendes (Revista Enfermagem Digital Cuidado e Promoção da Saúde, 2019)
Perform a systematic review to investigate the use of the Aldrete and Kroulik Index in the Post Anesthetic Recovery Room (PACU).Systematic review conducted in June 2018, with the DeCS / MeSH descriptors selected from their definitions, are as follows: Anesthesia recovery period; Recovery room; Nursing care; Patient discharge. The databases consulted were MEDLINE, LILACS, BDENF and SCIELO. The selection criteria were published between 2008 to 2017; main subject: anesthesia recovery period, PACU and patient discharge; Languages: Portuguese, English and Spanish.Seven articles were found within the established criteria. They reported the use of IAK associated with other scales such as pain, nausea, temperature and delusions. They pointed out deficiencies in the evaluation, such as absence of temperature and pain measurement. The benefits of using IAK were identified, besides raising a discussion about its limitations.